ALTERNATIF BUDIDAYA TANAMAN KACANG HIJAU (Phaseolus radiatus L.) SECARA ORGANIK - Ferinda Dewi Sari Harahap; Husna Yetti; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of the interaction of cow manure and active ingredients Trichoderma sp biofungisida and get a best dose or doses of cow manure biofungicide against the growth and production of green bean plants. The research was conducted at the Experimental Station of the Faculty of Agriculture, University of Riau, Pekanbaru. This study was conducted over three months, starting in August 2017 to October 2017. This study uses the randomized block design (RAK), factorial, consisting of two factors. The first factor was cow manure (P) which consists of three levels (0, 2.5, 5) ton / ha and the second factor Trichoderma biofungicide (B) which consists of three levels (0,2,4) g / l. The data were statistically analyzed using ANOVA and continued with HSD at the 5 % level. Parameters measured were plant height (cm), flowering date (day), harvesting (days), number of pods per plant (pod), the percentage of peas pithy per plant (%), weight of seeds per plant (g), dry weight of 100 seeds (g) and seed yield per plot (g). Based on research results indicate that administration of cow manure and Trichoderma sp. biofungisida active ingredients affected on plant height, date of harvest, number of pods per plant, seed weight per plant, 100-seed weight and seed yield per plot. Cow manure 5 tons / ha and Trichoderma active ingredients spbiofungicide. 4 g / l tends to be the highest yield in the growth and production of green beans. Keywords : green bean, cow manure, Trichoderma. sp